Adaptación de la técnica de Microinjertación in vitro de ápices caulinares, de Valencia y Pineapple utilizando patrones de Carrizo (Poncirus trifoliata (L.) Raf. x Citrus sinensis (L.) Osbeck) y Citrumelo (Poncirus trifoliata (L.) Raf. x Citrus paradisi Macf.) - Cortés-Paniagua, Ronny (Instituto Tecnológico de Costa Rica, 2004)
Shoot-tip grafting consists in growth of shoot tip onto decapited seedlings obtained from seeds. The successful of this procedure is produced because of the cellular multiplication is faster than virus multiplication. In this work, several parameters to improve the caulinar apex shoot-tip grafting technique of Valencia and Pineapple onto Carrizo and Citrumelo seedlings have been studied. The objective of this research was to improve the protocols of preparation of the rootstock, preparation of the shoot-tips and the culture under glasshouse conditions. The rootstocks were obtained from seeds, decoated and sterilized with sodium hypochlorite, individually cultured in darkness. The source of shoot tips was the flush from defoliated branches of field trees. The shoot-tip was inserted into an inverted-T made at the top of the decapited rootstock epicotyl. The grafted plants were allowed to develop in vitro under 24 hr daily exposure to illumination and were provided with a nutrient solution containing a high concentration (7,5 %) of sucrose. Grafted planted were transplantable to soil from 4 to 6 weeks after grafting and carried to glasshouse. It has been demonstrated that the successful on preparation of the rootstocks is related with sodium hypochlorite solution concentration, with number of people decoating seeds and time remaining after decoating and before sterilization. It has been established one protocol to obtain high frequencies of successful on preparation of the rootstocks. It was observed that the source of shoot tips used in this research wasn’t the better one, because of the trees are influenced by weather conditions. The culture of grafted plants under glasshouse conditions was successful when the plants were cultured under climatic conditions of windless, indirectly sun and high temperature.

La micro injertación in vitro de ápices caulinares consiste en el desarrollo de un meristemo apical colocado sobre el empicótelo decapitado de una planta originada a partir de semilla. El éxito del procedimiento obedece a que la tasa de multiplicación celular en el meristemo apical supera la del virus, escapando de la infección. En este trabajo se buscó adaptar la técnica de micro injertación in vitro de ápices de Valencia y Pineapple sobre patrones de Carrizo y Citrumelo. Se centró la atención en optimizar el método de producción de patrones, en la obtención y el manejo de los ápices y en el proceso de aclimatación de los micro injertos. Los patrones fueron obtenidos mediante la germinación de semillas, cultivadas individualmente en tubos de ensayo, en oscuridad. Los ápices de Valencia y Pineapple se obtuvieron de brotes de árboles mantenidos en campo. Los micro injertos se realizaron sobre patrones etiolados a los que se les realizó un corte en forma de T invertida. El cultivo de los micro injertos se efectuó en medio líquido bajo 24 horas luz. Los micro injertos exitosos se trasplantaron a macetas y se llevaron al invernadero. Se demostró que el éxito en la producción de patrones está condicionado por la concentración de la solución de desinfección, el número de personas involucradas en el pelado de las semillas y el tiempo que transcurre hasta su desinfección. De este modo se estableció un punto de equilibrio que permitió alcanzar un elevado número de patrones aptos. Se determinó que la obtención de ápices a partir de árboles mantenidos en el campo es una práctica que no asegura la disponibilidad permanente de explantes, debido a que estas plantas responden de manera diferencial a los fluctuantes cambios ambientales. En cuanto a la aclimatación de los micro injertos, se pudo observar que las condiciones de frío desfavorecen su desarrollo, mientras que lugares con temperaturas superiores a los 25 C constituyen las zonas más apropiadas para efectuar el proceso de aclimatación, así como para el cultivo de plantas micro injertadas
Proyecto de Graduación (Bachillerato en Ingeniería en Biotecnología) Instituto Tecnológico de Costa Rica. Escuela de Biología, 2004.
Keywords: Microbiología; Semillas; Desinfección; Equilibrio; Optimización; Germinación